2020
DOI: 10.5194/acp-20-2471-2020
|View full text |Cite
|
Sign up to set email alerts
|

Composition and mass size distribution of nitrated and oxygenated aromatic compounds in ambient particulate matter from southern and central Europe – implications for the origin

Abstract: Abstract. Nitro-monoaromatic hydrocarbons (NMAHs), such as nitrocatechols, nitrophenols and nitrosalicylic acids, are important constituents of atmospheric particulate matter (PM) water-soluble organic carbon (WSOC) and humic-like substances (HULIS). Nitrated and oxygenated derivatives of polycyclic aromatic hydrocarbons (NPAHs and OPAHs) are toxic and ubiquitous in the ambient air; due to their light absorption properties, together with NMAHs, they are part of aerosol brown carbon (BrC). We investigated the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 98 publications
7
28
0
Order By: Relevance
“…1). These results are in agreement with previous reports from other urban sites in central and southern Europe (Kitanovski et al 2020) and China (Li et al 2016). The aerosol number size distributions (characterised in Fig.…”
Section: Concentration Levels and Mass Size Distributionssupporting
confidence: 93%
See 3 more Smart Citations
“…1). These results are in agreement with previous reports from other urban sites in central and southern Europe (Kitanovski et al 2020) and China (Li et al 2016). The aerosol number size distributions (characterised in Fig.…”
Section: Concentration Levels and Mass Size Distributionssupporting
confidence: 93%
“…The determination of NMAHs in the PM filter samples was done using a validated analytical procedure (Kitanovski et al 2012(Kitanovski et al , 2020 with small modifications. In short, a 1.5-cm 2 section of the filter was spiked with 4-nitrophenol-d 4 (IS; spiked mass, 100 ng) and extracted three times (5 min each) with 10 mL methanolic solution of EDTA (3.4 nmol mL −1 ) in an ultrasonic bath.…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…rural, marine, urban) and in different seasons have shown that most (i.e. >80%) of particulate NOPAHs present in the air were bound to fine particles ( Albinet et al, 2008 ; Alves et al, 2016a ; Besis et al, 2017 ; Kitanovski et al, 2020 ; Lammel et al, 2020 , Lammel et al, 2017 ; Ringuet et al, 2012b ). Depending on availabilities, high volume air samplers (HVAS, Digitel DH77, flow rate of 30 m 3 h −1 at the Brno T site and the R site) or low volume air samplers (LVAS, Leckel MVS6 at Brno UB, LVS 3.1 Comde Derenda LVS/MVS at Ljubljana T and ECHO PM, Tecora at Ljubljana UB, all with a flow rate of 2.3 m 3 h −1 ) were used.…”
Section: Methodsmentioning
confidence: 99%